Acceptance Test Of Diagnostic X-Ray Merk GE Type XR 6000 In Radiodiagnostic And Radiotherapy Department Laboratory Of Health Polytechnic Of Semarang - M. Irwan Katili; Andrey Nino Kurniawan; Nanang Sulaksono (Poltekkes Kemenkes Semarang, 2014)
The purpose of this study is to test the X-ray equipment GE Type XR 6000 in in JTRR Laboratory of Health Polytechnic in Semarang the and analyze the test results. It is a quantitative measurement of some components including Collimator, X-ray tube and generator. The instruments used for the measurement were Piranha test tool, TOR ABC as well as the water passes. The measurement result for light is 281.67 lux, deviation for collimator ΔX + ΔY is 1.8% and a deviation of 1.5 degrees. For the measurement of tube leakage is still below the leak amounted to 1 mGy / h. The accuracy of all tubes is less than 5% (diff kVp). Tube current output is still appropriate with the setting. The linearity coefficient results in mAs linearity testing is less than 0.1. The CV value of reproducibility is ≤ 0.05. While the value of the measured HVL is already greater than 2.3 mmAl at 80 kVp. In conclusion, the results of the measurements of X-rays equipment Ge Type XR 6000 in JTRR Laboratory of Health Polytechnic of Semarang is still within the acceptance for use.